Three-dimensional functional gradients direct stem curling in the resurrection plant Selaginella lepidophylla. Issue 159 (30th October 2019) - Brulé, Véronique; Rafsanjani, Ahmad; Asgari, Meisam; Western, Tamara L.; Pasini, Damiano
Abstract : Upon hydration and dehydration, the vegetative tissue of Selaginella lepidophylla can reversibly swell and shrink to generate complex morphological transformations. Here, we investigate how structural and compositional properties at tissue and cell wall levels in S. lepidophylla lead to different stem curling profiles between inner and outer stems. Our results show that directional bending in both stem types is associated with cross-sectional gradients of tissue density, cell orientation and secondary cell wall composition between adaxial and abaxial stem sides. In inner stems, longitudinal gradients of cell wall thickness and composition affect tip-to-base tissue swelling and shrinking, allowing for more complex curling as compared to outer stems. Together, these features yield three-dimensional functional gradients that allow the plant to reproducibly deform in predetermined patterns that vary depending on the stem type. This study is the first to demonstrate functional gradients at different hierarchical levels combining to operate in a three-dimensional context.